Preliminary Approach to Reimagining of Polluted Soil Ecosystem: Identification and Utilization of Autochthonous Hydrocarbon Degrading Bacteria - Otugboyega, JOSEPH; Otugboyega, OLAIDE OLUWAYEMISI; AYO, ITUNNU O.; ALIU, KAMORU T. (FUDMA Journal of Sciences, 2026)
Crude-oil Pollution negatively impacts the ecosystems. This study sought to recover crude-oil impacted soil ecosystem, by isolating, screening and identifying indigenous bacteria in a microcosm experiment. Samples of agricultural soil, were thoroughly blended with bonny light crude-oil and allowed to equilibrate for three weeks. Physiochemical parameters (pH, Moisture content, Electrical Conductivity, heavy metals, Polycyclic Aromatic Hydrocarbons (PAHs) and Total Petroleum Hydrocarbons (TPH) of the control and contaminated soils were assessed using standard laboratory methods and Gas Chromatography-Mass Spectrometry (GC-MS). Hydrocarbon-utilizing bacteria (HUB) were isolated from the impacted soil using Bacto Bushnell Haas broth supplemented with 1% crude-oil as the nutrient medium. Isolates’ Morphological, Biochemical and molecular characterization, as well as degradation screening were done. Physical parameters for the control and impacted soils differed significantly (P
Keywords: Bioremediation; biotechnology; ecosystem restoration; hydrocarbon utilizing bacteria; Isolates’ characterization